ANALISA FRAUD DIAMOND DALAM PENDETEKSIAN TINDAKAN FINANCIAL SHENANIGANS - Kurniawati, Anggreni Dian (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
ABSTRACTConflicts of interest between investors as principals and management as agents that often benefit one party, triggering fraud in financial reporting. Fraudulent financial statements can be indicated by the existence of financial shenanigans, namely opportunistic earnings management actions that cause the financial statements presented to be inconsistent with the actual company performance. The study used four components of the fraud diamond that were suspected of causing financial shenanigans to occur in the company. This study will use the earnings manipulation shenanigans. The sample of this research is companies listed on the Indonesia Stock Exchange with the 2016-2018 observation period. Hypothesis testing is done by using multiple regression tests. The results of this hypothesis testing indicate that the two components of fraud diamond, namely pressure proxied by financial targets and rationalization, which is proxied by total accruals, have a positive effect on financial shenanigans. The results of this study fail to prove that the other two components of fraud diamond, namely opportunities that are proxied by nature of industry, have a negative effect on financial shenanigans and the change of directors has no effect on financial shenanigans. The results of this study are expected to be a reference for auditors in detecting fraudulent financial statements that occur because of financial shenanigans.Keywords: earning manipulation shenanigans; financial shenanigans; financial statement fraud; fraud diamondABSTRAKKonflik kepentingan antara investor selaku prinsipal dengan manajemen selaku agen yang seringkali menguntungkan satu pihak sehingga memicu terjadinya kecurangan dalam pelaporan keuangan. Kecurangan laporan keuangan dapat ditandai dengan adanya tindakan financial shenanigans yaitu tindakan manajemen laba oportunistik yang menyebabkan laporan keuangan yang disajikan tidak sesuai dengan kinerja perusahaan sebenarnya. Penelitian menggunakan empat komponen fraud diamond yang diduga menyebabkan terjadinya tindakan financial shenanigans yang terjadi di perusahaan. Penelitian ini akan menggunakan earnings manipulation shenanigans. Sampel penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesia dengan periode amatan tahun 2016-2018. Pengujian hipotesis dilakukan dengan menggunakan uji regresi berganda. Hasil pengujian hipotesis ini menunjukkan bahwa dua komponen fraud diamond yaitu tekanan yang diproksikan dengan target keuangan dan rasionalisasi yang diproksikan dengan total akrual berpengaruh positif terhadap financial shenanigans. Hasil penelitian ini tidak berhasil membuktikan bahwa dua komponen fraud diamond lainnya yaitu peluang yang diproksikan dengan nature of industry berpengaruh negatif terhadap financial shenanigans dan pergantian direksi tidak berpengaruh terhadap financial shenanigans. Hasil penelitian ini diharapkan dapat menjadi acuan auditor dalam melakukan pendeteksian terhadap kecurangan laporan keuangan yang terjadi karena adanya tindakan financial shenanigans ini.Kata kunci: earnings manipulation shenanigans; financial shenanigans; kecurangan laporan keuangan; fraud diamond